Improved Glucose Metabolism In Vitro and In Vivo by an Allosteric Monoclonal Antibody That Increases Insulin Receptor Binding Affinity - Corbin, John A. (Public Library of Science, 2014)
Previously we reported studies of XMetA, an agonist antibody to the insulin receptor (INSR). We have now utilized phage display to identify XMetS, a novel monoclonal antibody to the INSR. Biophysical studies demonstrated that XMetS bound to the human and mouse INSR with picomolar affinity. Unlike monoclonal antibody XMetA, XMetS alone had little or no agonist effect on the INSR. However, XMetS was a strong positive allosteric modulator of the INSR that increased the binding affinity for insulin nearly 20-fold. XMetS potentiated insulin-stimulated INSR signaling ∼15-fold or greater including; autophosphorylation of the INSR, phosphorylation of Akt, a major enzyme in the metabolic pathway, and phosphorylation of Erk, a major enzyme in the growth pathway. The enhanced signaling effects of XMetS were more pronounced with Akt than with Erk. In cultured cells, XMetS also enhanced insulin-stimulated glucose transport. In contrast to its effects on the INSR, XMetS did not potentiate IGF-1 activation of the IGF-1 receptor. We studied the effect of XMetS treatment in two mouse models of insulin resistance and diabetes. The first was the diet induced obesity mouse, a hyperinsulinemic, insulin resistant animal, and the second was the multi-low dose streptozotocin/high-fat diet mouse, an insulinopenic, insulin resistant animal. In both models, XMetS normalized fasting blood glucose levels and glucose tolerance. In concert with its ability to potentiate insulin action at the INSR, XMetS reduced insulin and C-peptide levels in both mouse models. XMetS improved the response to exogenous insulin without causing hypoglycemia. These data indicate that an allosteric monoclonal antibody can be generated that markedly enhances the binding affinity of insulin to the INSR. These data also suggest that an INSR monoclonal antibody with these characteristics may have the potential to both improve glucose metabolism in insulinopenic type 2 diabetes mellitus and correct compensatory hyperinsulinism in insulin resistant conditions.